We will solve the problem using the substitution method.
The system of equations to be solved is
![\begin{cases}3x-y=6 \\ -2x+2y=8\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/h5c6ag5704mggdrwcjxaslzpbsu659hp9a.png)
Notice that the second equation is equivalent to
![\begin{gathered} -2x+2y=8 \\ \Leftrightarrow(1)/(2)(-2x+2y)=(1)/(2)(8) \\ \Leftrightarrow-x+y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nbbgbi0u8ykx632ot0hcr84ttq5ywmrf9g.png)
Then,
![\Rightarrow y=4+x](https://img.qammunity.org/2023/formulas/mathematics/college/h80h58rcbe1fpu6w9ikhyis7zxi6lisvhc.png)
We can substitute the last result into the first equation of the system as shown below
![\begin{gathered} 3x-y=6 \\ \Rightarrow3x-(4+x)=6 \\ \Rightarrow3x-4-x=6 \\ \Rightarrow2x=6+4=10 \\ \Rightarrow x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3ar15ggptlxi8866hckvxpp9h5y3rueuct.png)
Finally,
![\begin{gathered} \Rightarrow y=4+(5)=9 \\ \Rightarrow y=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a29dmht82px6ukx7y2gx5nolr32irutiy5.png)
The answer is (x,y)=(5,9)